2017
DOI: 10.1371/journal.pone.0182003
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of a schistosome circulating cathodic antigen rapid test kit at point-of-care for mapping of schistosomiasis endemic districts in The Gambia

Abstract: BackgroundStudies in Sub Saharan Africa have shown that the Circulating Cathodic Antigen point-of-care-test (POC-CCA) is more accurate in the detections of S. mansoni than the microscopic Kato-Katz technique but less is known about the accuracy of this rapid test in detecting S. haematobium infections. This study was intended to evaluate the field accuracy of POC-CCA as a rapid test kit for schistosomiasis mapping in The Gambia.MethodsThis prospective study was conducted in 4 regions in the country. Ten school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
(32 reference statements)
3
30
0
Order By: Relevance
“…haematobium infections should be known. On the other hand, several studies indicated that POC-CCA test is not reliable in detecting S. haematobium infections [ 16 , 42 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…haematobium infections should be known. On the other hand, several studies indicated that POC-CCA test is not reliable in detecting S. haematobium infections [ 16 , 42 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the POC-CCA assay is inconsistent for the detection of infection with S. haematobium. [38][39][40][41] Thus, because the standard urine filtration assay for S. haematobium eggs is, like the KK, insensitive at low-to-moderate levels of infection intensity, 42,43 a tool is still needed for mapping S. haematobium in low prevalence areas.…”
Section: Additional Considerations In Using Poc-cca For Mappingmentioning
confidence: 99%
“…Also, POC-CCA accuracy may be questionable in areas of S . haematobium mono infection or multiple Schistosoma infections [ 11 13 ]. But discussion becomes really intense when RTs are used in low parasite load and/or low endemic areas.…”
Section: Use Of Novel Approaches In the Diagnosis Of Schistosomiasis:mentioning
confidence: 99%